Building information modelling for sustainability appraisal of conceptual design of steel-framed buildings - Oti, Akponanabofa Henry (2014)
In the construction sector, capturing the building product in a single information model with good interoperable capabilities has been the subject of much research efforts in at least the last three decades. Contemporary advancements in Information Technology and the efforts from various research initiatives in the AEC industry are showing evidence of progress with the advent of building information modelling (BIM). BIM presents the opportunity of electronically modelling and managing the vast amount of information embedded in a building project, from its conception to end-of-life. Researchers have been looking at extensions to expand its scope. Sustainability is one such modelling extension that is in need of development. This is becoming pertinent for the structural engineer as recent design criteria have put great emphasis on the sustainability credentials in addition to the traditional criteria of structural integrity, constructability and cost. Considering the complexity of nowadays designs, there is a need to provide decision support tools to aid the assessment of sustainability credentials. Such tools would be most beneficial at the conceptual design stage so that sustainability is built into the design solution starting from its inception. This research work therefore investigates how contemporary process and data modelling techniques can be used to map and model sustainability related information to inform the structural engineer’s building design decisions at an early stage.